Divulgação científica para o público infantil: um estudo de caso no Museu da Amazônia (MUSA) - Magalhães, Cíntia Emanuelly Ramos (2013)
This research focuses on the Scientific Divulgation to child audience from a case study in the Museu Da Amazônia (MUSA). The aim is centered on understanding the ways in which this museum, when interact with the child audience, including them in their educational dimension, has performed Scientific Divulgation, contributed to arouse the curiosity of this public to science and valued cultural capital of amazonian children. Regarding to methodological perspective, it was built an investigative itinerary founded on the qualitative research through the following instruments: document analysis, direct observation and interview. The collected datas were processed based on empirical-interpretative analysis. Considering the elements analyzed, the results indicate that the Museu Da Amazônia, while performing Scientific Divulgation to children, contributes to the stimulation of imagination and curiosity of children, favors their interest in science topics and also gives them the opportunity for expansion of cultural capital. Such possibilities arises from the fact the museum studied is an open environment that allows interactivity between children and the living beings in their natural habitat, to privilege in their exposure the culture of amazonian people and be located in a peripheral area of the city of Manaus. Thus, the Museu da Amazônia presents itself as an instrument with transforming and liberating potential of the reproductions processes of social inequalities, being a cultural facility of Scientific Divulgation for amazonian children.